Biophilic concept as a public space design / Adisti Ananda Yusuff, Erina Wiyono and Jhon Viter Marpaung - Yusuff, Adisti Ananda; Wiyono, Erina; Marpaung, Jhon Viter (Faculty of Art and Design, 2023)
The COVID-19 pandemic that occurred at the end of 2019 has made many changes in all aspects of life, from offices, education, entertainment, and even how to socialize in daily activities. One sector that is quite impacted is commercial space. Some commercial spaces were forced to stop their activities due to the high number of COVID cases that hit Jakarta in particular. But over time, cases have now begun to decline and improve. This has made many commercial industries start to revive to start new habits and lives after the previous pandemic. public areas are one of the places that are now starting to reopen after almost 2 years of social restrictions, one of which is a cafe which is a gathering place and socializes for most people in Indonesia, especially in the city of Jakarta. With the reopening of cafes today many offers new concepts to make it comfortable and safe for visitors who come. The biophilic concept is taken because this concept is very appropriate to be realized during a pandemic. With an open area, the air circulation that customers get feels safe, besides that the use of open space is also beneficial both in terms of lighting and air circulation which is expected to be one of the answers to the new concept that will be used in the future after the pandemic. The methodology used is a qualitative method with a phenomenological approach. Qualitative observation data is collected by documenting all kinds of information and conducting direct surveys on the location. The purpose of this research can be useful for future public space design and become a design reference for the current era of new habits. and hopefully, in the future, this research can always be improved and updated along with the development of technology that is increasingly developing.